Regional dialect of modern Lviv: language-contact processes - Palinska, Olesya; Kaczala, Oleg (Видавництво Львівської політехніки, 2013)
The theoretical aspects of the multilinguizm are considered in the article, particularly the distinguishing of such sociolinguistic phenomena as code-switching, codemixing and congruent lexicalization are examined. The history of formation and the modern state of Lviv regional dialect is analyzed.
Keywords: language contacts; code-switching; code-mixing; congruent lexicalization; copula; quasi-article